CH4 and N2O fluxes from Lake Licheńskie, Lake Łódzko-Dymaczewskie, Lake Dębno and Lake Trześniowskie - Woszczyk, Michał (PANGAEA, 2024)
Table presents average monthly diffusive fluxes (F) of CH4 and N2O from Lake Licheńskie (LLi), Lake Łódzko-Dymaczewskie (LLD), Lake Dębno (LD) and Lake Trześniowskie (LT). The water samples from LLi were collected between December 2014 and November 2015 as well as between March 2022 and February 2023. The samples from LLD, LD and LT were collected between July 2019 and July 2020. The flux values were calculated with first Fick's law of diffusion for different values of k600 (acc. to Crusius & Wanninkhof 2003, Cole & Caraco 1998, Brasse et al. 2017 and Vachon & Praire 2013). As U10 we used averaged monthly wind speed values for the town of Koło and Powidz (for LLi), Poznań (for LLD and LD) as well as Słubice and Babimost (for LT) obtained from https://en.tutiempo.net/climate/poland.html). Ceq were calculated on the basis of mean atmospheric concentrations of CH₄ and N₂O over Europe in 2015 (1.859·10-6 and 3.264·10-7 bar, respectively; https://www.eea.europa.eu/data-and-maps/daviz/atmospheric-concentration-of-carbon-dioxide-5#tab-chart_6; CH₄ concentrations reported for 2015 and N₂O concentrations for 2009) and relevant Henry constants (KH). The KH values, adopted from Sander (2015) were 0.0014 mol·L-1·bar-1 for CH₄ and 0.025 mol·L-1·bar-1 for N₂O.
Keywords: Anthropogenic impact; fluxes; Lake; Methane; nitrous oxide